2018
DOI: 10.2500/aap.2018.39.4183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient satisfaction with his or her inhaler on adherence and asthma control

Abstract: Background: Asthma guidelines recommend considering patient preferences for inhaler choice. However, few studies have assessed the impact of patient satisfaction with an inhaler on adherence and health outcomes. Objective: To assess the impact of patient satisfaction with an inhaler on adherence and health outcomes in asthma. Methods: In a cross-sectional, observational, multicenter study, 778 patients with moderate or severe asthma and who were treated with maintenance inhalers completed a number of scales an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
(36 reference statements)
2
43
0
1
Order By: Relevance
“…Among other features, ease of use, convenient weight and size, and ease of portability contributed to higher satisfaction with EH. These results confirm the findings in the whole ASCONA population, where patient satisfaction was also higher with EH than with TH or DKAH [9]. Moreover, although the aim of our study was not to prove the clinical relevance of differences in FSI-10 score, results of ASCONA main analysis [9] showed that these differences are clinically relevant.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Among other features, ease of use, convenient weight and size, and ease of portability contributed to higher satisfaction with EH. These results confirm the findings in the whole ASCONA population, where patient satisfaction was also higher with EH than with TH or DKAH [9]. Moreover, although the aim of our study was not to prove the clinical relevance of differences in FSI-10 score, results of ASCONA main analysis [9] showed that these differences are clinically relevant.…”
Section: Discussionsupporting
confidence: 89%
“…A relationship between satisfaction and adherence has been found in other studies [3,27], but these did not compare different inhalers. In the main analysis of ASCONA, high patient satisfaction with inhaler was related to adherence and asthma control [9]. However, because of the sample size in our subanalysis, the difference in satisfaction was insufficient to be reflected in adherence and asthma control.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Satisfaction with inhaler is defined as how satisfied patients' are with their inhaler devices regarding ease and convenient to use. Inhaler satisfaction is very important part of the treatment with chronic airway diseases, enhancing both adherence and disease control 12,31 . Inhaler satisfaction differs between different inhaler devices in asthma and COPD patients 21,22 .…”
Section: Discussionmentioning
confidence: 99%